Basisteoretiese perspektiewe vir beoordeling van 'n kerklike Psalmboek - J. H. van Rooy; B. J. de Klerk (Acta Theologica)
n 2003 the Gereformeerde Kerke in Suid-Afrika (Reformed Churches in South Africa) introduced a new hymn book Psalmboek 2003 (Psalter 2003). For the evaluation of the use of this hymn book as communication medium in a liturgical service, six basic theoretical perspectives were formulated from Scripture, utilising the model of Zerfass (1974). This article discusses these perspectives and the Scriptural data they are based on. Three of them are related to functional aspects of the song, two with form and communication and one with the expansion of the Old Testament Psalter in the New Testament. These three aspects can be used for the evaluation of a hymn book, as well as individual hymns.